2017
DOI: 10.1007/s11665-017-3017-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Material Constitutive Laws for Inconel 718 Superalloy Under Different Strain Rates and Working Temperatures

Abstract: In this paper, a special procedure for the prediction of parameters of the Johnson-Cook constitutive material models is proposed based on the experimental data and specially developed MATLAB scripts which allow advanced modeling of complex 3D response surfaces. Experimental investigations concern two various strain rates of 10 23 and 10 1 1/s and the testing temperature ranging from the ambient up to 700°C. As a result, a set of mathematical equations which fit the experimental data is determined. The applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In addition to the choice of shear angle relationship, the selection of suitable material parameters among the many existing Johnson-Cook (J-C) constitutive laws in [33,45] for Inconel 718 also affects the predicted shear flow stress and cutting constants, which can differ by as much as 20% for the annealed 718 and 50% for the aged 718 at room temperature within a typical effective strain range of 1 to 1.5 in a machining application. These J-C parameters are mostly derived from SHPB tests with the maximum strains lower than 1, and with the maximum strain rates only reaching 3000 [27], 4600 [46,47], or 5000 [48] 1/s.…”
Section: Comparison Of Predicted and Identified Cutting Constantsmentioning
confidence: 99%
“…In addition to the choice of shear angle relationship, the selection of suitable material parameters among the many existing Johnson-Cook (J-C) constitutive laws in [33,45] for Inconel 718 also affects the predicted shear flow stress and cutting constants, which can differ by as much as 20% for the annealed 718 and 50% for the aged 718 at room temperature within a typical effective strain range of 1 to 1.5 in a machining application. These J-C parameters are mostly derived from SHPB tests with the maximum strains lower than 1, and with the maximum strain rates only reaching 3000 [27], 4600 [46,47], or 5000 [48] 1/s.…”
Section: Comparison Of Predicted and Identified Cutting Constantsmentioning
confidence: 99%
“…The methodology of the determination of thermal conductivity and diffusivity using the LF method is described in Ref. [6]. In contrast, the diffusivity of pure aluminium decreases but its values are ten times higher than for a titanium alloy.…”
Section: Measurement and Visualization Techniquesmentioning
confidence: 99%
“…16 Also, the model takes account of different extents of thermomechanical settings stipulated by the metal removal process, besides the model is adequately capable of continuous chip modeling and continues to be recognized in the literature. 17,18 Grzesik et al 19 chose JC constitutive model to examine the cutting forces and temperatures through the machining of Inconel 718 alloy. The authors revealed a high degree of similarity between the predicted and the experimental values.…”
Section: Introductionmentioning
confidence: 99%